Speaking up or staying silent? citizens’ engagement of pro-biafra protests and farmers-herders crises in the user-generated content of selected Nigerian online newspapers (2019)
The public space provided by the Web 2.0 technologies where citizens freely interact and discuss public issues such as politics, security and national unity is one of the beauties of modern democracy. However, this freedom has produced some counter-value cultures. Existing studies on new media, citizen journalism and political discourse generally have focused largely on citizens’ construction of nationhood, but with scant attention given to how the citizens use the comment sections of the news media to engage issues relating agitation for secession and security issues in Nigeria. This study, therefore, examined how Nigerians used the comment sections of selected Nigerian online newspapers to interact and discuss issues of agitation for secession and Farmers-herders crises in the country with a view to determining how the issues got the citizens to speak up or to stay silent. Textual and quantitative content analyses of the user-generated contents of Sahara Reporters and Premium Times show that generally, majority of the readers were found to be highly hostile towards other readers outside their ethnic groups while negotiating separation issues, but less hostile on the insecurity issues. To create fear of dominance, words within Exonyms classification were predominantly used by the readers while interacting among themselves on the insecurity issues. To evoke a sense marginalization, words within Endonyms category were employed by the readers to discuss issues of agitation for secession. Nigerian government should pay critical attention to the dynamics of the virtual community in its quest to ensure national peace and unity.